2020
DOI: 10.1186/s12889-020-8390-9
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reach and motivate migrant communities at high risk for TB to participate in a latent tuberculosis infection screening program: a community-engaged, mixed methods study among Eritreans

Abstract: Background: In the Netherlands, migrant populations with a high tuberculosis (TB) incidence are an important target group for TB prevention. However, there is a lack of insight in effective community-engaged strategies to reach and motivate these migrants to participate in latent TB infection (LTBI) screening and treatment programs. Methods: In cocreation with Eritrean key figures and TB staff, we designed and executed six strategies to reach and motivate Eritrean communities to participate in LTBI programs, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 13 publications
0
61
1
1
Order By: Relevance
“…It has been reported that one of the major challenges in ensuring adherence especially for LTBI treatment is to overcome the psychological resistance held by patients to take drugs for a non-contagious and nonsymptomatic infection that may never develop into active disease, but which could cause potential adverse effects, and convince them of the potential bene ts of prevention [13]. This is could be especially challenging especially when targeting patients who come from culture that is unfamiliar with the concept of screening and prevention [18]. For example, a prospective study that has examined the predictors for non-completion of LTBI treatment has concluded that a perceived risk of progression to active TB is strongly associated with better adherence [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that one of the major challenges in ensuring adherence especially for LTBI treatment is to overcome the psychological resistance held by patients to take drugs for a non-contagious and nonsymptomatic infection that may never develop into active disease, but which could cause potential adverse effects, and convince them of the potential bene ts of prevention [13]. This is could be especially challenging especially when targeting patients who come from culture that is unfamiliar with the concept of screening and prevention [18]. For example, a prospective study that has examined the predictors for non-completion of LTBI treatment has concluded that a perceived risk of progression to active TB is strongly associated with better adherence [19].…”
Section: Discussionmentioning
confidence: 99%
“…(8) Although interviewees experienced felt and enacted stigma, which could impede treatment start and completion (25,26), strong motivation resulted in high uptake and completion rates. (16,17) To successfully implement TB prevention programs and to overcome persisting stigmatizing community norms about TB, interventions focused on knowledge-shaping and attitude changing are needed. (25,27) Educators -such as TB care staff and community-workers-should appropriately portray messages: emphasizing the contagiousness of TB rather than effective prevention measures may fail to subduct stigmatizing behaviours and could create even more fear.…”
Section: Participant On Ltbi Treatment: "When Some Friends Offer You mentioning
confidence: 99%
“…It incorporated three mixed method studies (qualitative and quantitative research methods), which evaluated the implementation among 1) immigrants (15), 2) asylum seekerspredominantly Eritreans-living in asylum seeker centres (16), and 3) Eritrean refugees living in communities for maximum of ten years. (17) For this paper we used data from semi-structured interviews with Eritrean asylum seekers living in asylum seeker centres (15) and Eritrean refugees living in communities (17) in the Netherlands. Eritreans from both studies were predominantly from the same cohort (arrival in The Netherlands 2013-2017) of Eritrean asylum seekers characterized by a great proportion of male young Christian adults, literate but mostly without higher education, from a rural background, from the ethnic group Tigrinya.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) To reduce the individual TB burden and the country's incidence, LTBI screening and treatment is being implemented in the Netherlands among immigrants 18 years and younger. Following the need to increase efforts to reduce the TB incidence and the positive results of three implementation studies (7)(8)(9), Dutch policy advisors are now debating about expanding the implementation of post-arrival LTBI screening to other subgroups of immigrants and asylum seekers.…”
Section: Introductionmentioning
confidence: 99%